Acute appendicitis and secondary peritonitis in a patient with end-stage renal failure and a dormant peritoneal dialysis catheter - Olang, Catherine; Kiarie, Patrick; Bhatia, Shubham; Fultz, Oliver; Louis, Martine A. (International Surgery Journal, 2025)
Peritoneal dialysis (PD) is a common renal replacement therapy for patients with end-stage renal disease (ESRD). Despite its benefits, PD-related peritonitis remains a severe complication, often associated with significant morbidity and mortality. Although most cases of PD-related peritonitis are due to touch contamination, intra-abdominal infections, such as appendicitis, are less common but can result in severe outcomes. We present a case of severe peritonitis secondary to perforated appendicitis in a patient with a dormant PD catheter. A 41-year-old male with ESRD, previously on PD, presented with a 36-hour history of fever, chills, nausea, and abdominal pain. Despite transitioning to hemodialysis, the patient had retained his PD catheter, which had not been used for months. On admission, the patient was septic with evidence of peritonitis. Blood cultures were positive for Escherichia coli, while PD catheter cultures were negative. An abdominal CT scan revealed a gangrenous perforated appendix. The patient underwent an emergency laparoscopic appendectomy and PD catheter removal, resulting in significant clinical improvement. Perforated appendicitis in ESRD patients with a PD catheter can result in severe peritonitis with life-threatening complications, including sepsis and cardiac events. This case underscores the importance of maintaining a high index of suspicion for intra-abdominal causes of peritonitis in PD patients, even when the PD catheter is dormant. Timely diagnosis, empiric antibiotic therapy, and prompt surgical management are essential to reduce mortality in these patients.